EFFECTIVE CONTROL, TREATMENT AND PREVENTION OF ANEMIA IN HEART FAILURE AND DISEASES IN THE FERGANA VALLEY - Axunbayev Otabek Adilovich (Web of Journals Publishing, 2025)
This study examines anemia correction protocols in 284 cardiovascular patients across three clinical centers in the Fergana Valley during 2022-2024. Combined iron supplementation with erythropoiesis-stimulating agents demonstrated hemoglobin elevation from 98.4 g/L to 118.7 g/L over 16 weeks, alongside reduced hospitalization rates by 34% and improved functional capacity in NYHA class II-III patients with concurrent heart failure and iron deficiency anemia.
Keywords: anemia, heart failure, iron deficiency, cardiovascular diseases, erythropoiesis-stimulating agents, hemoglobin, ferritin, NYHA classification, Fergana Valley, cardiorenal syndrome, hospitalization, quality of life, ferrous sulfate, intravenous iron, treatment outcomes.